Sociodrama technique in health instruction - Prodigalidad, Beatriz Ong (1971)
The topic of this paper was on how sociodrama may be utilized as a technique in health instruction through the use of bibliographical method of research. Data were gathered from various sources, both published and unpublished. It included professional books and journals. Sociodrama should be used in a natural situation when a point needs clarification than when it is artificially created. Role players may be chosen by the group, or the students may volunteer. The audience needs preparation so that observations are meaningful. The unique characteristic of sociodrama is that it is unrehearsed. For better results, the activities were organized in 3 phases, namely, the warm-up, the action and the follow-up phases.
Vita.
Thesis (M.A. Health Education)--University of the Philippines, Diliman.
Keywords: Health education -- Philippines; Sociodrama -- Philippines; Drama in education